The Influence of Visionary Leadership and Quality of Education on Organizational Culture - Najib Abdulloh; Siswanto Siswanto; Nailatul Muna; Kathryn Colvin (Yayasan Keluarga Guru Mandiri, 2025)
Organizational culture plays a crucial role in determining the sustainability and innovation of educational institutions, particularly in the face of increasingly dynamic challenges. This study aims to analyze the influence of visionary leadership and the quality of education on organizational culture. A quantitative approach with an explanatory design was employed in this study, and hypothesis testing was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis. Data was collected from 100 respondents using purposive sampling techniques and analyzed using SmartPLS software. The study's results show that both visionary leadership and the quality of education have a significant impact on organizational culture, with visionary leadership having a more pronounced influence. These findings confirm that leaders who possess a clear vision and can inspire organizational members can shape values, norms, and behaviors that foster a strong and adaptive organizational environment. Quality education fosters a strong culture by instilling shared values and enhancing organizational cohesion. This research contributes to the development of a theoretical framework by integrating leadership perspectives and educational quality in the study of organizational culture. Practically, the research results provide insights for educational institutions to enhance organizational performance through leadership development strategies and improve the quality of education.